Chitinase-like protein YKL-40 regulates human bronchial epithelial cells proliferation, apoptosis, and migration through TGF-β1/Smads pathway. (April 2020) - Guan, R; Lin, R; Jin, R; Lu, L; Liu, X; Hu, S; Sun, L
In order to study the effects of chitinase-like protein YKL-40 on proliferation, apoptosis, and migration of human bronchial epithelial cell line (BEAS-2B), and the underlying mechanisms, we cultured BEAS-2B alone or with different concentrations of YKL-40. thiazolyl blue tetrazolium bromide (MTT) assay was used to examine the cell proliferation. Annexin V-fluorescein isothiocyanate isomer (FITC)/propidium iodide staining and scratch assay were performed to test the cell apoptosis and migration. The concentrations of transforming growth factor-β1 (TGF-β1), Smad3, Smad7, alpha-smooth muscle actin (α-SMA), interleukin-4 (IL-4), IL-6, and IL-8 in the cell culture supernatant were detected by enzyme-linked immunosorbent assay. The messenger RNA and protein levels of YKL-40, TGF-β1, Smad3, Smad7, and α-SMA were detected by reverse transcription polymerase chain reaction and Western blot. BEAS-2B cells cultured with different concentrations of YKL-40 showed significantly higher cell proliferation and migration and inflammatory cytokines compared with that of control group, while the cell apoptosis was significantly lower than that of control group ( p < 0.05). In addition, BEAS-2B cells cultured with YKL-40 had increased TGF-β1, Smad3, Smad7, and α-SMA levels in the supernatant, compared with that of BEAS-2B cells cultured alone ( p < 0.05). Furthermore, LY364947, as TGF-β1/Smads signaling pathway inhibitor, decreased cell proliferation and migration ability and enhanced cell apoptosis of BEAS-2B cells compared with control group ( p < 0.05). However, YKL-40 administration reversed the effect of LY364947 on the biological behavior of BEAS-2B cells. YKL-40 could affect the biological behaviors of BEAS-2B cells, which might be related to the TGF-β1/Smads pathway.